Sharing in the company determinants, processes and outcomes of employee participation - Kato, Takao active 2017; Poutsma, Erik; Ligthart, Paul E. M. (Advances in the economic analysis of participatory & labor-managed firms)
Prelims -- Sharing in the company : introduction to the volume -- Employee ownership and high-performance work systems in context -- Which companies adopt sharing arrangements and why? -- Who participates in share plans and why? -- How has employee share ownership evolved in the global context? -- Firm foundations for democracy? worker ownership and control in advanced capitalism -- Index